Educating People for Food Security to Avert Food Crisis: The Case of Nigeria - B. Ubong; N.S. Oguzor; A.M. Wokocha (University of Sofia, 2009)
The year 2008 has been dubbed "the year of global food crisis" by many writers probably because the supply of food around the world dipped precariously leading to sharp increases in food prices around the world that triggered riots and related problems. Certainly many countries particularly in Africa, Latin America, and Asia have been depending on food handouts for decades but the situation appears not to have been as acute as it was in 2008. The need for a new paradigm in food aid has been noted by some NGOs that have initiated effort to make food aid more pragmatic and have broader benefit to recipient countries. On a more extensive and sustained level, there is the need to give young people in developing countries an early orientation in food security by emphasizing agriculture generally and food production in particular in the school curriculum. The paper uses Nigeria as a case study and hopes recommendations herein can be applied in other developing countries